PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT SEMEN BATURAJA TBK TAHUN 2013-2022 - RIZQY FATHI BOWI SIHOTANG; Arif Surahman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to analyze the effect of cash turnover and receivables turnover on profitability, proxied by Return On Assets (ROA), at PT Semen Baturaja Tbk during the 2013–2022 period, both partially and simultaneously. The study employed an associative quantitative method using secondary data in the form of the company’s annual financial statements obtained from the company’s official website. The data analysis technique applied was multiple linear regression, supported by partial testing (t-test), simultaneous testing (F-test), and the coefficient of determination.The results indicate that, partially, cash turnover has a negative and significant effect on ROA, with an absolute t-value of 4.921 exceeding the t-table value of 2.30600 and a significance value of 0.002, which is lower than 0.05; therefore, H1 is accepted. Receivables turnover has an effect on ROA but is not statistically significant, as indicated by a t-value of 2.352 exceeding the t-table value of 2.30600 and a significance value of 0.051, which is greater than 0.05; therefore, H2 is rejected. Simultaneously, cash turnover and receivables turnover have a significant effect on ROA, with an F-value of 39.911 exceeding the F-table value of 4.74 and a significance value of 0.001, which is lower than 0.05; therefore, H3 is accepted. The R Square value of 0.896 indicates that 89.6% of the variation in ROA can be explained by both variables, while the remaining 10.4% is influenced by other variables outside the scope of this study. Keywords: Cash Turnover, Accounts Receivable Turnover, Return On Assets, Profitability